EFFECTS OF LONG-TERM ANTIPSYCHOTIC TREATMENT ON ENKEPHALIN-IMMUNOREACTIVE NEURONS IN RATS PERINATALLY TREATED WITH PHENCYCLIDINE - Kompanijec, Anja; Korica, Bojan; Stojkovic , Tihomir (Medicinski podmladak, 2023)
Introduction: Schizophrenia is a chronic mental illness that affects 1% of the world population. The phencyclidine animal model of schizophrenia is based on the glutamate theory of the development of schizophrenia. Enkephalin is a neuropeptide with a role in the development of schizophrenia symptoms via the modulatory effect of neurotransmission. Aim: This study aimed to elucidate whether the long-term treatment with haloperidol and risperidone causes the difference in the appearance of enkephalin-immunoreactive neurons (EIN) in the brain of rats perinatally treated with phencyclidine (PCP). Material and methods: Experimental Wistar rats were treated on postnatal days 2 (PN2), 6, 9, and 12 with either PCP (10 mg/kg) or saline. From PN35 to PN100 haloperidol (3 mg/kg) and risperidone (1 mg/kg) were administrated orally in drinking water. Animals were divided into six groups. The control group received saline and drinking water, PCP group received PCP and drinking water. Hal group received saline and haloperidol, PCP-Hal group PCP and haloperidol, while Ris group and PCP-Ris received saline or PCP and risperidone. All animals were sacrificed at PN100 and the cortex, hippocampus, striatum, and septal area were used to analyze the presence of EIN by immunohistochemistry. Results: In the hippocampus, the number of EIN was significantly higher in the PCP group than in the control group. Antipsychotics had a potent effect in the septal area, where both of them decreased the area covered by the EIN compared to the control group. In the striatum, only haloperidol changed the level of EIN by increasing the area covered with these neurons compared to the covered area in the control group. Conclusion: Long-term administration of antipsychotics caused the region-specific change in the distribution of enkephalin-immunoreactive neurons in the brain of a rat, perinatally treated with PCP.